Feasibility of community diagnosis in ensuring prioritization of health concerns: Perspective of developing countries - Saurabh R Shrivastava; Prateek S Shrivastava; Jegadeesh Ramasamy (Wolters Kluwer Medknow Publications, 2014)
A community refers to a group of people who share the same stakes and concerns, the members of which knows and interact with each other. The process of diagnosing the health, health-related problems and their determinants, in a community is called community diagnosis, whose ultimate aim is to identify where the community is now?, where does it want to be?, and how it will get there? The principles of community diagnosis have been tried and found of extreme utility in developing countries where multiple health problems are prevalent, but only scarce resources are available. To conclude, the process of community diagnosis enables developing countries in reaching a consensus about the priority health problems in their individual communities and in developing strategies to address the identified issues.